RESISTENSI INTERAKSI UMAT HINDU MELALUI REPRODUKSI PRAKTIK KEAGAMAAN DALAM TRADISI PANGKONAN DI DESA ADAT CAU BELAYU - Ni Made Sinar Sari; Ni Luh Sri Kusuma Dewi; Ni Wayan Mia Restiya Damayanti; I Gede Sutana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The influence of globalization does not only change the physical style of humans as a subject that responds to global influences. But in other aspects it is also affected, one of which is the aspect of social interaction in a homogeneous cultural space. This is a strategy for local policy makers to respond to this influence to continue to hold social interactions in the local religious culture space by holding the tradition of mapangkon or pangkonan in Hindu religion in the Cau Belayu Traditional Village, Marga District, Tabanan Regency. The power of globalization that requires humans to experience social mobility so that social interaction becomes tenuous, on the legitimacy of society, the implementation of the mapangkon tradition takes place to build and promote the resistance of communal social interactions.Keywords: Building Hindu People Interaction, Pangkonan Ceremony